2000
DOI: 10.1073/pnas.97.3.1091
|View full text |Cite
|
Sign up to set email alerts
|

Actin coating of secretory granules during regulated exocytosis correlates with the release of rab3D

Abstract: The present study describes a novel phenomenon in pancreatic acinar cells undergoing regulated exocytosis. When acinar cell preparations were challenged with the secretagogue carbamylcholine, a subpopulation of zymogen granules became coated with filamentous actin. These zymogen granules were always in proximity of the acinar cell apical membrane (the site of exocytosis) but did not appear to have fused yet. They were distinct from regular zymogen granules not only because of their association with filamentous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
109
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 33 publications
7
109
3
Order By: Relevance
“…Rab proteins, in particular Rab3, have been postulated to play a role in regulated exocytosis in the pancreatic acinar cell (34,46,47) and can potentially interact with acinar SNARE proteins (18). Jamieson et al have recently reported that Rab3 is required for actin coating of the apical ZGs (46). Whereas more work is needed to identify additional regulatory proteins involved in apical exocytosis, we have gained further insights into a regulator, Munc18c, that we believed to be involved in basolateral exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Rab proteins, in particular Rab3, have been postulated to play a role in regulated exocytosis in the pancreatic acinar cell (34,46,47) and can potentially interact with acinar SNARE proteins (18). Jamieson et al have recently reported that Rab3 is required for actin coating of the apical ZGs (46). Whereas more work is needed to identify additional regulatory proteins involved in apical exocytosis, we have gained further insights into a regulator, Munc18c, that we believed to be involved in basolateral exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Mature LG acinar cell SV localize beneath an actin-rich network underlying the APM; on stimulation, SV appear to undergo compound fusion followed by exocytosis of their contents at the APM (25). Myosin motors and actin filaments are believed to facilitate terminal aspects of SV fusion with APM and content extrusion; studies in LG acinar cells have collectively suggested that stimulation with the muscarinic agonist, carbachol (CCH), results in transient disassembly of the actin barrier beneath the APM concurrent with the assembly of actin "coats," which aid in the compound fusion of SV homotypically and with the APM (24,46,52). Both the unconventional myosin motor, myosin 5C, and non-muscle myosin II are thought to participate in aspects of terminal SV fusion (24,29).…”
mentioning
confidence: 99%
“…Although this F-actin coat is thought to constitute a barrier to exocytosis (4 -7), secretory granules undergo exocytosis selectively at the apical membrane (8 -10). Redistribution of F-actin is induced during intense secretory activity (4,11,12), but it has remained unknown how F-actin regulates exocytosis in exocrine cells.…”
mentioning
confidence: 99%